High frequency of the exoU plus /exoS plus genotype associated with multidrug-resistant high-risk clones of Pseudomonas aeruginosa clinical isolates from Peruvian hospitals - Horna, Gertrudis (2019)
The type III secretion system of Pseudomonas aeruginosa is an important virulence factor contributing to the cytotoxicity and the invasion process of this microorganism. The current study aimed to determine the presence of the exoU+/exoS+ genotype in P. aeruginosa clinical isolates. The presence of exoS, exoT, exoU and exoY was determined in 189 P. aeruginosa by PCR, and the presence/absence of exoU was analysed according to source infection, clonal relationships, bioflm formation, motility and antimicrobial susceptibility. The gyrA, parC, oprD, efux pump regulators and β-lactamases genes were also analysed by PCR/sequencing. The exoS, exoT and exoY genes were found in 100% of the isolates. Meanwhile, exoU was present in 43/189 (22.8%) of the isolates, being signifcantly associated with multidrug resistance, extensively drug resistance as well as with higher level quinolone resistance. However, the presence of β-lactamases, mutations in gyrA and parC, and relevant modifcations in efux pumps and OprD were not signifcantly associated with exoU+ isolates. MLST analysis of a subset of 25 isolates showed 8 diferent STs displaying the exoU+/exoS+ genotype. The MDR basis of the exoU+ isolates remain to be elucidated. Furthermore, the clinical implications and spread of exoU+/exoS+ P. aeruginosa isolates need to be established.